2020
DOI: 10.31234/osf.io/qv5t7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Who Is the Most Stressed During COVID-19 Isolation? Data From 27 Countries

Abstract: To limit the rapid spread of COVID-19, countries have asked their citizens to stay at home. As a result, demographic and cultural factors related to home life became especially relevant to predicting population well-being during isolation. This pre-registered worldwide study analyses the relationship between the number of adults and children in a household, marital status, age, gender, individualism-collectivism and perceived stress. We used the COVIDiSTRESS Global Survey data of 54,245 online participants fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Our results are consistent with other studies that have collected data over a similar period, but in other countries around the world and on non-student populations. Notably, Kowal et al ( 42 ) observed that being a woman, living in a collectivist culture, being single and living with children were associated with higher levels of stress. Higher stress in women appears to be observed robustly in other work ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with other studies that have collected data over a similar period, but in other countries around the world and on non-student populations. Notably, Kowal et al ( 42 ) observed that being a woman, living in a collectivist culture, being single and living with children were associated with higher levels of stress. Higher stress in women appears to be observed robustly in other work ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…At that time, transmission rates of COVID-19 were growing exponentially (Liu et al, 2020). Scholars observed high stress levels among people all around the world (Kowal et al, 2020), and increased psychological distancing to nations most affected by the pandemic (Sorokowski et al, 2020), what, altogether, may indicate an international crisis. For these reasons, our study provides an interesting opportunity to shed some more insight into a well-known phenomenon in political science -the socalled "rally 'round the flag" -an increased support for national leaders in times of a severe crisis (Mueller, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…It quite naturally leads to expecting detrimental effects for creativity, given 4 CREATIVE LOCKDOWN that creative people are usually tolerant (Groyecka, 2018) and liberal rather than conservative (Dollinger, 2007) and use a variety of creative thinking strategies (Jankowska et al, 2018). What's more, there is solid evidence that thinking about COVID increases the level of stress (Kowal et al, 2020), a factor negatively related to creative thinking (Duan et al, 2020). A recent study that tested whether activating thinking about coronavirus influences people's insight and analytical problem solving (Karwowski et al, 2020) found a negative effect, yet only among men.…”
Section: A Daily Diary Study Of Creative Activity During Pandemicsmentioning
confidence: 99%